PENGELOLAAN HUTAN KOTA BERKELANJUTAN: TINJAUAN ASPEK TEKNIS, ALAM DAN SOSIAL (Studi di Hutan Kota Srengseng dan Hutan Kota Universitas Indonesia) - Sukarta, D. K. (Bumi Lestari; Vol 13 No 1 (2013), 2013)
Abstract This study was conducted at Srengseng Urban Forest and Universitas Indonesia Urban Forest, to indentify the structure of the urban forest, its effectiveness in lowering city temperatures, and to predict the people behavior towards urban forest using the thoery of planned behavior. The approach which is used in this study is aquantitative approach and is also supported by qualitative data. The method which is used is observasional field study and data collected by closed questionnaires and interview techniques. Our study observes a total of 24sample plots, consisting of 4 plots examples in SrengsengUrban Forest and 20 sample plotsin Universitas Indonesia Urban Forest. The number of respondents in total90 people, comprised of 47 respondents in Srengseng Urban Forest and 43 respondents in Universitas Indonesia Urban Forest. Vegetation analysis implementedby observing the condition of the stands includes plant species,diameter, and height of plants ranging from seedling stotrees. It’s continued by an analysis of the diversity, distribution, and dominance of vegetation using theShannon diversity index, dominance index, and the important value index. The results of the vegetation analysis shows that Universitas Indonesia Urban Forest has a higher diversity of vegetation t han in Srengseng Urban Forest. The relationship between the technical aspects which is density and the natural aspects which are the temperature showed that temperature is related to density. The analysis of the social aspects describe that respondents have a good perception of the urban forest although the behavior seems inconsistent withhis perception. Statistical test results showed that the behavior of the respondents are influenced by subjective norms that existin their community.
Keywords: Keywords: urban forest, density, temperature,behavior